The personal history, adventures, experience and observation of David Copperfield [videorecording] - Dickens, Charles 1812-1870.; Cubor, George; Estabrook, Howard; Selznick, David O.; Walpole, Hugh. (New York Packaged by MGM/UA Home Video)
David Copperfield enjoys an idyllic life with his gentle, widowed mother and his loving nurse, Peggoty. Then tragedy strikes when Mr. Murdstone, a monster of cruelty, weds David's mother, and drives her to death. David is forced to live in misery and poverty until he runs away to himself upon the mercy of his eccentric aunt. His adventures introduces us to every stratum of Victorian society.
VHS.
Film editor, Robert Kern.
W.C. field as Micauber Lionel Barrymore as Dan Peggoty, Maureen O'Sullivan, as Dora, Madge Evans as Agnes, Edna May Oliver as Aunt Betsy, Lewis Stone as Mr. Wickfield, Frank Lawton as David (man), Freddie Bartholomew as David (child).
Keywords: Young men -- England -- Motion Pictures